RISK FACTORS FOR THE DEVELOPMENT OF RENAL PATHOLOGY, CARDIOVASCULAR AND CEREBROVASCULAR SYSTEMS - Malikaxon Mirxamzayevna, Mamurova; Mavludaxon Mirxamzayevna, Mamurova; Bobir Temirpulotovich, Turayev (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to identify and analyze common risk factors contributing to the development of renal pathology, cardiovascular diseases, and cerebrovascular disorders, highlighting the interconnected pathophysiological mechanisms among these systems. Method: A comprehensive literature review and comparative analysis were conducted to examine the overlapping pathogenetic pathways and shared risk factors across renal, cardiovascular, and cerebrovascular conditions. The study synthesized data from peer-reviewed articles, clinical studies, and epidemiological reports to identify key mechanisms influencing disease progression. Results: The analysis revealed that risk factors such as hypertension, diabetes mellitus, dyslipidemia, smoking, and chronic inflammation are common to all three systems, contributing to endothelial dysfunction, atherosclerosis, and impaired vascular regulation. These shared mechanisms underscore the parallel progression of pathology within the brain, heart, and kidneys, increasing the susceptibility to comorbid conditions. Novelty: This study provides new insights into the integrated pathophysiological processes linking renal, cardiovascular, and cerebrovascular diseases, emphasizing the need for holistic prevention strategies and multidisciplinary management approaches to address these interrelated health risks effectively.